Public Perception of Health And Sickness in The Context of RiverWater Use For Needs - Kartinah Kartinah; Ike Anggraini Gunawan; Annisa Nurrachmawati (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : The use of polluted river water for household purposes is still frequently found in various regions of Indonesia. Objective : This narrative review aims to explore community perceptions regarding the meaning of health and sickness in relation to the practice of using river wate Research Methods/ Implementation Methods : The literature review indicates that communities develop unique perceptions of water quality based on sensory indicators (color, smell) and direct experience, rather than microbiological parameters. Results : The concept of 'sickness' tends to be defined functionally as a condition that disrupts daily activities, while mild illnesses like diarrhea and skin rashes are often normalized. Socio-cultural, economic factors, and limited knowledge shape these perceptions and create a cycle of dependency on river water. Conclusion/Lesson Learned : It is concluded that there is a gap between scientific health definitions and community perceptions, therefore public health interventions need to consider participatory approaches that understand the construction of health-sickness meanings at the community level.